Robust Channel Registration and Clutter Suppression for Airborne Terahertz Multichannel SAR-GMTI - Zhenjiang Li; Chenggao Luo; Hongqiang Wang; Heng Zhang; Chuanying Liang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
Airborne terahertz (THz) synthetic aperture radar (SAR) demonstrates significant potential for real-time ground moving target indication due to its high frame rate and superior resolution. The performance of the system is driven by its high pulse repetition frequency and short wavelength, which introduce two key characteristics: enhanced Doppler sensitivity and a broad nonclutter region. First, the Doppler sensitivity amplifies group phase shift error between channels caused by nonideal platform motion, leading to reduced interchannel data correlation. To achieve precise phase correction, an adaptive iterative phase spectrum compensation method is proposed. Then, due to the broad nonclutter region in the THz band, conventional methods are only effective in the clutter-dominated region, which elevates the noise floor in the nonclutter region. To ensure the high signal-to-clutter-noise ratio of the moving target, a weighted displaced phase center antenna method based on wavelet decomposition is proposed. Finally, the moving target is detected and preliminarily imaged. Real-measured THz-SAR data processing results are presented to validate the effectiveness and feasibility of the proposed methods.